2012
DOI: 10.1177/1464420712451807
|View full text |Cite
|
Sign up to set email alerts
|

Influence of injection process parameters on dimensional stability of wax patterns made by the lost wax process using Taguchi approach

Abstract: Investment casting is a manufacturing technique employed to produce near net shape metal components. Wax is the most widely used pattern material. In the present work, the wax blend, to be used in the investment casting process, is prepared by mixing different waxes and starch as filler material to reduce the shrinkage of wax patterns. The effect of the selected injection process parameters on the dimensional stability of the wax patterns made by the investment casting process using silicon rubber mould has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…3 produced by mixing 25% of paraffin wax, 5 % of carnauba wax, 35% of microcrystalline wax, 12% of polyethylene wax and 23% of starch showed least shrinkage and remarkable surface finish. 19 It has also been found that the aforementioned wax blend possessed low-ash content and viscosity followed by sufficient hardness. Hence, further experiments were carried out using blend no.…”
Section: Methodsmentioning
confidence: 95%
“…3 produced by mixing 25% of paraffin wax, 5 % of carnauba wax, 35% of microcrystalline wax, 12% of polyethylene wax and 23% of starch showed least shrinkage and remarkable surface finish. 19 It has also been found that the aforementioned wax blend possessed low-ash content and viscosity followed by sufficient hardness. Hence, further experiments were carried out using blend no.…”
Section: Methodsmentioning
confidence: 95%
“…According to equation (7), if f kÁj (u j (k)) is derivable at the point u t j (k), the Taylor series expansion of equation ( 9) can be shown…”
Section: State Space Equationmentioning
confidence: 99%
“…The effect of wax injection processing parameters on the final dimensions and dimensional stability of the wax part was indicated by some experimental investigations. 5,6 Pattnaik et al 7 found the optimum levels of the process parameters on shrinkage of wax parts via the signal-to-noise and the analysis of variance method. Furthermore, Chen et al 8,9 used the mathematical model to describe the relationship between process parameters and dimension shrinkage variation of injection molded wax part with thin shell feature via response surface methodology.…”
Section: Introductionmentioning
confidence: 99%
“…Yarlagadda and Hock [8] found the correctness of wax patterns manufactured by hard and soft tooling and further optimized the injection process parameters to achieve good dimensional accurateness of the patterns. Further, Pattnaik et al [9][10][11] determined the best wax blend composition made from different types of waxes and fillers and also optimized the injection process parameters so as to reduce pattern shrinkage at the same time improving surface finish and hardness.…”
Section: Introductionmentioning
confidence: 99%